2012
DOI: 10.1017/s1751731111002692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, body weight and body condition score before mating start date on the pubertal rate of maiden Holstein–Friesian heifers and implications for subsequent cow performance and profitability

Abstract: The aim of this study was to assess the influence of age, body weight (BW) and body condition score (BCS) of maiden Holstein-Friesian heifers before mating start date (MSD) on the rate of puberty, subsequent production and longevity and their implications with regard to farm profitability. Data were available on 871 Holstein-Friesian heifers from 48 herds. BW was recorded electronically and BCS was recorded by a single operator on a scale of 1 to 5. Heifer age was calculated as the number of days from birth to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
3
30
1
3
Order By: Relevance
“…Although not validated against estrus or pregnancy outcomes during the breeding period following examination, Archbold et al [6] estimated the sensitivity of ultrasonography to determine pubertal status to be reduced during pro-estrus and metestrus, due to the relatively poor ability to visualise the regressing corpus albicans and the corpus haemoragicum respectively. We therefore assume that the reason why the absence of a follicle ≥13 mm remained an independent predictor in our models was either that some heifers that were pubertal at the time of examination had their first estrus in the few days after the examination, or that in postpubertal heifers a CL was not detected due to stage of the estrus cycle.…”
Section: Individual Independent Predictors Of Reproductive Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not validated against estrus or pregnancy outcomes during the breeding period following examination, Archbold et al [6] estimated the sensitivity of ultrasonography to determine pubertal status to be reduced during pro-estrus and metestrus, due to the relatively poor ability to visualise the regressing corpus albicans and the corpus haemoragicum respectively. We therefore assume that the reason why the absence of a follicle ≥13 mm remained an independent predictor in our models was either that some heifers that were pubertal at the time of examination had their first estrus in the few days after the examination, or that in postpubertal heifers a CL was not detected due to stage of the estrus cycle.…”
Section: Individual Independent Predictors Of Reproductive Outcomesmentioning
confidence: 99%
“…Reproductive tract score (RTS) predicts anestrus and pregnancy failure in heifers independently of age, body weight (BW) and body condition score (BCS), and is a valid selection tool to enhance reproductive performance of herds [3][4][5][6][7]. However, estrus cycle stage and proportion of heifers in anestrus affect the accuracy of RTS, the complexity of the RTS system affects its repeatability, and other tests with potential to improve RTS are available [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…An efficient heifer rearing system is essential to meet these targets and ensure that replacement heifers maximise their potential as lactating animals. Archbold et al (2012) demonstrated that larger, well grown heifers had greater pubertal rates at mating start date (MSD), and were more profitable over their lifetime due to superior milk production and greater longevity.…”
Section: Improved Biosecuritymentioning
confidence: 99%
“…These heifer calves will be closely grouped in terms of age, and it would therefore be easier to manage them as one group to meet the optimal target of 60% of mature BW at MSD (Archbold et al, 2012).…”
Section: Improved Biosecuritymentioning
confidence: 99%
“…The effects of inadequate nutrition in cattle include delayed puberty Archbold et al, 2012), prolonged postpartum anovulation (Rhodes et al, 2003), reduced body condition score (BCS) , and poor submission and conception rates (Buckley et al, 2003). Dairy production systems based on grazed pasture are primarily located in countries where environmental conditions support long growing seasons.…”
Section: Introductionmentioning
confidence: 99%